High-toughness thermally-formed hazel stone basin and preparation method thereof

By adding specific ingredients to the Zhenshi Basin formula and performing high-temperature sintering treatment, the problem of insufficient toughness of Zhenshi Basin in the prior art is solved, and a Zhenshi Basin with high toughness and corrosion resistance is achieved.

CN119462069AActive Publication Date: 2025-02-18GUANGDONG OVERLAND CERAMICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411493867.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-18
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

In the prior art, Zhenshi Basin has shortcomings in toughness and other aspects, resulting in a short service life.

Method used

By adding active composition powder, modified kaolin, modified bentonite and modification additives to the Zhenshi Basin formula, and mixing and sintering at a specific temperature and sonication treatment, a high-toughness thermoformed Zhenshi Basin is formed.

Benefits of technology

It significantly improves the toughness and strength of Zhenshi Basin, extends its service life, and improves corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a high-toughness thermoforming hazel stone basin and a preparation method thereof. The preparation method comprises the following steps: taking an active composition, modified kaolin, modified bentonite, a performance additive, sodium alcohol ether carboxylate, a titanate coupling agent, isopropanol, artemisia seed gum, aluminum silicate, lithium tantalate and copper calcium titanate; through the working procedures of mixing, ultrasonic treatment, cold storage treatment, pre-forming pressing, gradient roasting, demolding and the like, the high-strength and high-toughness acid-resistant and alkali-resistant high-strength stone basin is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of stone basin preparation, and specifically relates to a high-toughness hot-formed stone basin and a preparation method thereof. Background Art

[0002] Artificial stone is a kind of stone made by artificial synthesis. It is usually made by mixing natural stone particles or powder with resin, cement or other adhesives. There are many types of artificial stone, each with its own specific application areas and characteristics.

[0003] Artificial quartz stone: It is made by mixing quartz particles (usually more than 93%) with resin and pressing. It has high hardness and wear resistance, is not easy to scratch, and has strong pollution resistance. It is very suitable for home decoration such as kitchen countertops and bathroom countertops. Resin artificial stone: It is mainly composed of resin (such as unsaturated polyester resin) and filler (such as aluminum hydroxide). It has a soft texture and is easy to process and shape. It is often used to make kitchen countertops, sinks, bathtubs, etc. Composite artificial stone: This type of stone usually contains a combination of multiple materials, such as resin, quartz powder, marble powder, etc., which is both beautiful and practical and widely used. Terrazzo: Although terrazzo in the traditional sense is cast and polished on site, modern technology also allows prefabricated terrazzo slabs. It is made of crushed stone, glass or other hard materials mixed with cement or resin binder, and is often used for architectural decoration such as floors and walls. Ceramic artificial stone: It is made by high-temperature firing, has the characteristics of high strength and wear resistance, and its appearance can imitate the texture of natural stone. It is often used for floor and wall decoration.

[0004] At present, household sanitary ware is also one of the main areas of artificial stone. Conventional artificial stone on the market is synthesized with different unsaturated resins and calcium carbonate and aluminum hydroxide. The sanitary products made from it have low hardness, poor toughness and short service life. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a high-toughness thermoformed Zhenshi basin in view of the shortcomings of the Zhenshi basin in the prior art in terms of toughness, etc. By adding active composition powder, modified kaolin, modified bentonite and modified additives and other ingredients to the Zhenshi basin formula, a Zhenshi basin with excellent toughness and strength is obtained.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-toughness thermoformed stone basin comprises the following steps: S1: preparing active composition powder; S2: Preparation of modified kaolin; S3: preparing modified bentonite; S4: preparing a modification aid; S5: In parts by weight, 25-45 parts of the active composition obtained in step S1, 20-40 parts of the modified kaolin obtained in step S2, 15-25 parts of the modified bentonite obtained in step S3, 5-10 parts of the modified auxiliary agent obtained in step S4, 3-6 parts of sodium alcohol ether carboxylate, 2-5 parts of titanate coupling agent, 15-35 parts of isopropanol and 2-6 parts of artemisia seed gum are mixed, and stirred at a temperature of 90-120°C for 30-50 minutes; then 3-6 parts of aluminum silicate, 2-7 parts of lithium tantalate and 3-8 parts of copper calcium titanate are added, and ultrasonic treatment is carried out at a power of 200-400W and a frequency of 85-95kHz for 15-25 minutes; then, a constant temperature refrigeration treatment is carried out at a temperature of 0.2-0.6°C for 75-95 minutes to obtain a mixture; S6: Pour the mixture obtained in step S5 into a mold for pre-forming and pressing, first sinter at a constant temperature of 1100-1250℃ for 15-25min; heat to 1350-1500℃ at a rate of 6-10℃ / min, and continue sintering at a constant temperature for 25-35min; cool to 850-920℃ at a rate of 5-8℃ / min and continue sintering at a constant temperature for 10-16min; then demold, cool to room temperature, grind and polish to obtain the high-toughness hot-formed Zhenshi basin.

[0007] Preferably, the preparation process of the active composition powder in step S1 is: grinding 10-20 parts of wollastonite, 5-10 parts of ultra-white sand, 3-8 parts of feldspar and 2-7 parts of diopside powder to a particle size of 80-100 nm, and subjecting the mixture to constant temperature steam treatment at a temperature of 280-300° C. for 8-12 min; cooling the mixture to 105-110° C. at a rate of 8-10° C. / min, and continuing the constant temperature steam treatment for 15-22 min; and subsequently subjecting the mixture to microwave treatment at a power of 200-230 W for 5-10 min, microwave treatment at a power of 560-600 W for 10-15 min, and microwave treatment at a power of 400-430 W for 12-18 min to obtain the active composition powder.

[0008] Preferably, the preparation process of the active composition powder is optimized as follows: 15 parts of wollastonite, 8 parts of ultra-white sand, 6 parts of feldspar and 5 parts of diopside powder are ground to a particle size of 80-100 nm, and subjected to constant temperature steam treatment at a temperature of 290° C. for 10 min; the temperature is lowered to 108° C. at a rate of 9° C. / min, and the constant temperature steam treatment is continued for 18 min; and then microwave treatment is performed at a power of 220 W for 7 min, microwave treatment at a power of 580 W for 12 min, and microwave treatment at a power of 420 W for 15 min to obtain the active composition powder.

[0009] Preferably, the preparation process of the modified kaolin described in step S2 is: crush the kaolin to a particle size of 5-10 μm, add a nitric acid aqueous solution with a mass fraction of 20-35% according to a solid-liquid ratio of 1g:5-8ml, stir evenly, magnetize for 8-16 minutes under a magnetic field strength of 2.2-2.8T, and dry at a temperature of 130-150°C for 25-35 minutes to obtain modified kaolin.

[0010] Preferably, the preparation process of the modified kaolin is optimized as follows: crush the kaolin to a particle size of 5-9 μm, add a 30% mass fraction nitric acid aqueous solution according to a solid-liquid ratio of 1g:7ml, stir evenly, magnetize for 14 minutes under a magnetic field strength of 2.5T, and dry at a temperature of 140°C for 30 minutes to obtain modified kaolin.

[0011] Preferably, the preparation process of the modified bentonite in step S3 is as follows: adding bentonite to an ethanol aqueous solution with a mass fraction of 25-35% according to a solid-liquid ratio of 1g:3-7ml and stirring evenly, keeping the temperature at 135-145°C for 8-12min, heating to 220-240°C at a rate of 2-5°C / min and continuing to keep the temperature for 30-40min, cooling to room temperature, immersing in an acetic acid aqueous solution with a mass fraction of 10%-15%, stirring evenly, and drying at a temperature of 100-120°C for 35-45min to obtain the modified bentonite.

[0012] Preferably, the preparation process of the modified bentonite is optimized as follows: adding bentonite to a 30% by mass ethanol aqueous solution at a solid-liquid ratio of 1g:5ml and stirring evenly, keeping the temperature at 140°C for 10min, heating to 230°C at a rate of 4°C / min and continuing to keep the temperature at 35min, cooling to room temperature, immersing in a 12% by mass acetic acid aqueous solution and stirring evenly, and drying at 110°C for 40min to obtain the modified bentonite.

[0013] Preferably, the preparation process of the modifying agent described in step S4 is: by weight, take 30-50 parts of calcium feldspar, 25-35 parts of mullite, 15-25 parts of calcium feldspar, 10-20 parts of montmorillonite and 1-3 parts of talc and mix them in a ball mill until they are uniform; after drying, put them into a mold, heat them to 1300-1500°C at a rate of 5-10°C / min, and keep them warm for 35-45min to obtain the modifying agent.

[0014] Preferably, step S5 is further optimized as follows: in parts by weight, 40 parts of the active composition obtained in step S1, 35 parts of the modified kaolin obtained in step S2, 22 parts of the modified bentonite obtained in step S3, 8 parts of the modified auxiliary agent obtained in step S4, 5 parts of sodium alcohol ether carboxylate, 4 parts of titanate coupling agent, 20 parts of isopropanol and 4 parts of artemisia seed gum are mixed, and stirred at a temperature of 110°C for 45 minutes; then 5 parts of aluminum silicate, 5 parts of lithium tantalate and 6 parts of calcium copper titanate are added, and ultrasonic treatment is carried out at a power of 350 W and a frequency of 92 kHz for 22 minutes; then, the mixture is refrigerated at a constant temperature of 0.4°C for 80 minutes to obtain a mixture.

[0015] Preferably, step S6 is further optimized as follows: pouring the mixture obtained in step S5 into a mold for pre-forming and pressing, first sintering at a constant temperature of 1200°C for 20 minutes; heating to 1480°C at a rate of 8°C / min, and continuing to sinter at a constant temperature for 28 minutes; cooling to 880°C at a rate of 6°C / min and continuing to sinter at a constant temperature for 12 minutes.

[0016] Compared with the prior art, the advantages and beneficial effects of the present invention are: Under the synergistic effect of the active composition, modified kaolin, modified bentonite and modified additives, the present invention can significantly increase the toughness and strength of the Zhenshi basin, effectively improving its performance and service life; by further adding titanate coupling agent, isopropyl alcohol, aluminum silicate, lithium tantalate and calcium copper titanate, the overall strength and toughness of the Zhenshi basin are further improved, and the corrosion resistance is effectively improved. Sodium alcohol ether carboxylate and artemisia seed gum can reduce internal defects of the material, effectively transfer stress, avoid cracks, and improve bending strength; The commonly used processes of the present invention are blanking, ball milling, powder spraying, forming, glazing, printing, firing (water absorption rate <0.03, complete vitrification), sorting, plate thickness>14mm, the rock plate is placed on the high-temperature refractory plate, and under the process treatment of the hot bending furnace, the rock plate falls to the high-temperature refractory plate by its own weight, and then cooled and formed, holed, trimmed, and edged; After the second hot bending, the rock slab's resistance to deformation, toughness and ductility are all relatively good. Different sizes and basin shapes can be customized. The product qualification rate can reach more than 98%. After high temperature, it will be overburned, causing it to become brittle and swollen, and it will not fall off the high-temperature refractory board. The glaze will be overburned, bubbled, and have pinholes. The glaze will crack. After the second hot bending, it will be brittle and cracked. After cooling, it will crack and have holes. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] The raw materials used in the present invention are as follows: Sodium alcohol ether carboxylate came from Hubei Wande Chemical Co., Ltd. with item number WD4395; titanate coupling agent came from Shanghai Dongjindu New Material Technology Co., Ltd. with item number 14; Artemisia seed gum came from Anhui Runtai Biotechnology Co., Ltd. with item number 2875; bentonite came from Shandong Zhengxing New Materials Co., Ltd. with item number CG8; talc came from Shanghai Yuanye Biotechnology Co., Ltd. with item number S33232.

[0019] Example 1 The present invention provides a method for preparing a high-toughness thermoformed stone basin, the steps of which are as follows: S1: 10 g of wollastonite, 5 g of ultra-white sand, 3 g of feldspar and 2 g of diopside powder were ground to a particle size of 80-100 nm, and subjected to constant temperature steam treatment at 280°C for 8 min; the temperature was lowered to 105°C at a rate of 8°C / min, and the constant temperature steam treatment was continued for 15 min; then, the mixture was subjected to microwave treatment at a power of 200 W for 5 min, at a power of 560 W for 10 min, and at a power of 400 W for 12 min to obtain an active composition powder; S2: Crush kaolin to a particle size of 5-10 μm, add 20% by mass nitric acid aqueous solution according to a solid-liquid ratio of 1g:5ml, stir evenly, magnetize for 8 minutes under a magnetic field strength of 2.2T, and dry at a temperature of 130°C for 25 minutes to obtain modified kaolin; S3: Add bentonite to a 25% ethanol aqueous solution at a solid-liquid ratio of 1g:3ml and stir at a rate of 800r / min, keep the temperature at 135℃ for 8min, increase the temperature to 220℃ at a rate of 2℃ / min and continue to keep the temperature for 30min, cool to room temperature, immerse in a 10% acetic acid aqueous solution and stir at a rate of 600r / min, dry at 100℃ for 35min, and obtain modified bentonite; S4: 30 g of calcium feldspar, 25 g of mullite, 15 g of calcium feldspar, 10 g of montmorillonite and 1 g of talc were mixed in a ball mill until uniform; after drying, they were put into a mold, heated to 1300° C. at a rate of 5° C. / min, and kept warm for reaction for 35 min to obtain a modified additive; S5: 25 g of the active composition obtained in step S1, 20 g of the modified kaolin obtained in step S2, 15 g of the modified bentonite obtained in step S3, 5 g of the modified auxiliary agent obtained in step S4, 3 g of sodium alcohol ether carboxylate, 2 g of titanate coupling agent, 15 g of isopropanol and 2 g of artemisia seed gum were mixed, and stirred at a temperature of 90°C and a speed of 800 r / min for 30 min; then 3 g of aluminum silicate, 2 g of lithium tantalate and 3 g of calcium copper titanate were added, and ultrasonic treatment was performed at a power of 200 W and a frequency of 85 kHz for 15 min; then, a constant temperature refrigeration treatment was performed at a temperature of 0.2°C for 75 min to obtain a mixture; S6: Pour the mixture obtained in step S5 into a mold for pre-forming and pressing, first sinter at a constant temperature of 1100°C for 15 minutes; heat it to 1350°C at a rate of 6°C / min, and continue sintering at a constant temperature for 25 minutes; cool it to 850°C at a rate of 5°C / min and continue sintering at a constant temperature for 10 minutes; then demold, cool to room temperature, grind and polish, and you can get the high-toughness hot-formed Zhenshi basin.

[0020] Example 2 The present invention provides a method for preparing a high-toughness thermoformed stone basin, the steps of which are as follows: S1: 20g of wollastonite, 10g of ultra-white sand, 8g of feldspar and 7g of diopside powder were ground to a particle size of 80-100nm, and subjected to constant temperature steam treatment at 300°C for 12min; the temperature was lowered to 110°C at a rate of 10°C / min, and the constant temperature steam treatment was continued for 22min; then the mixture was subjected to microwave treatment at a power of 230W for 10min, at a power of 600W for 15min, and at a power of 430W for 18min to obtain an active composition powder; S2: Crush kaolin to a particle size of 5-10 μm, add 35% by mass nitric acid aqueous solution according to a solid-liquid ratio of 1g:8ml, stir evenly, magnetize for 16 minutes under a magnetic field strength of 2.8T, and dry at a temperature of 150°C for 35 minutes to obtain modified kaolin; S3: Add bentonite to a 35% ethanol aqueous solution at a solid-liquid ratio of 1g:7ml and stir evenly, keep the temperature at 145°C for 12min, increase the temperature to 240°C at a rate of 5°C / min and continue to keep the temperature for 40min, cool to room temperature, immerse in a 15% acetic acid aqueous solution and stir evenly, dry at 120°C for 45min to obtain modified bentonite; S4: 50g of calcium feldspar, 35g of mullite, 25g of Nig, 20g of montmorillonite and 3g of talc were mixed in a ball mill until uniform; after drying, they were put into a mold, heated to 1500°C at a rate of 10°C / min, and kept warm for 45min to obtain a modified additive; S5: 45 g of the active composition obtained in step S1, 40 g of the modified kaolin obtained in step S2, 25 g of the modified bentonite obtained in step S3, 10 g of the modified auxiliary agent obtained in step S4, 6 g of sodium alcohol ether carboxylate, 5 g of titanate coupling agent, 35 g of isopropanol and 6 g of artemisia seed gum are mixed, and stirred at a temperature of 120°C and a speed of 500 r / min for 50 min; then 6 g of aluminum silicate, 7 g of lithium tantalate and 8 g of copper calcium titanate are added, and ultrasonic treatment is carried out at a power of 400 W and a frequency of 95 kHz for 25 min; then, a constant temperature refrigeration treatment is carried out at a temperature of 0.6°C for 95 min to obtain a mixture; S6: Pour the mixture obtained in step S5 into a mold for pre-forming and pressing, first sinter at a constant temperature of 1250°C for 25 minutes; heat it to 1500°C at a rate of 10°C / min, and continue sintering at a constant temperature for 35 minutes; cool it to 920°C at a rate of 8°C / min and continue sintering at a constant temperature for 16 minutes; then demold, cool to room temperature, grind and polish, and you can get the high-toughness hot-formed Zhenshi basin.

[0021] Example 3 The present invention provides a method for preparing a high-toughness thermoformed stone basin, the steps of which are as follows: S1: 15g of wollastonite, 8g of ultra-white sand, 6g of feldspar and 5g of diopside powder were ground to a particle size of 80-100nm, and subjected to constant temperature steam treatment at 290°C for 10min; the temperature was lowered to 108°C at a rate of 9°C / min, and the constant temperature steam treatment was continued for 18min; then, the mixture was subjected to microwave treatment at a power of 220W for 7min, at a power of 580W for 12min, and at a power of 420W for 15min to obtain an active composition powder; S2: Crush kaolin to a particle size of 5-10 μm, add 30% by mass nitric acid aqueous solution according to a solid-liquid ratio of 1g:7ml, stir evenly, magnetize for 14 minutes under a magnetic field strength of 2.5T, and dry at a temperature of 140°C for 30 minutes to obtain modified kaolin; S3: Add bentonite to a 30% ethanol aqueous solution at a solid-liquid ratio of 1g:5ml and stir evenly, keep the temperature at 140°C for 10min, increase the temperature to 230°C at a rate of 4°C / min and continue to keep the temperature at 35min, cool to room temperature, immerse in a 12% acetic acid aqueous solution and stir evenly, and dry at 110°C for 40min to obtain modified bentonite; S4: 45g of calcium feldspar, 28g of mullite, 22g of Nig, 15g of montmorillonite and 2g of talc were mixed in a ball mill until uniform; after drying, they were loaded into a mold, heated to 1460°C at a rate of 8°C / min, and kept warm for 42 minutes to obtain a modified additive; S5: 40 g of the active composition obtained in step S1, 35 g of the modified kaolin obtained in step S2, 22 g of the modified bentonite obtained in step S3, 8 g of the modified auxiliary agent obtained in step S4, 5 g of sodium alcohol ether carboxylate, 4 g of titanate coupling agent, 20 g of isopropanol and 4 g of artemisia seed gum were mixed, and stirred at a temperature of 110°C and a speed of 500 r / min for 45 min; then 5 g of aluminum silicate, 5 g of lithium tantalate and 6 g of copper calcium titanate were added, and ultrasonic treatment was performed at a power of 350 W and a frequency of 92 kHz for 22 min; then, a constant temperature refrigeration treatment was performed at a temperature of 0.4°C for 80 min to obtain a mixture; S6: Pour the mixture obtained in step S5 into a mold for pre-forming and pressing, first sinter at a constant temperature of 1200°C for 20 minutes; heat it to 1480°C at a rate of 8°C / min, and continue sintering at a constant temperature for 28 minutes; cool it to 880°C at a rate of 6°C / min and continue sintering at a constant temperature for 12 minutes; then demold, cool to room temperature, grind and polish, and you can get the high-toughness hot-formed Zhenshi basin.

[0022] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S1, only 10 g of wollastonite, 5 g of ultra-white sand, 3 g of feldspar and 2 g of diopside powder are ground to a particle size of 80-100 nm, and treated with constant temperature steam at a temperature of 280° C. for 8 min; and no subsequent treatment is performed.

[0023] Comparative Example 2 The difference between this comparative example and Example 1 is that step S2 directly uses kaolin without modification, and the other steps are the same.

[0024] Comparative Example 3 The difference between this comparative example and Example 1 is that bentonite is directly used in step S3 without modification, and the other steps are the same.

[0025] Comparative Example 4 The difference between this comparative example and Example 1 is that in step S4, 30 g of anorthite, 25 g of mullite, 15 g of anorthite and 10 g of montmorillonite are directly mixed without using talc, and the other steps are the same.

[0026] Comparative Example 5 The difference between this comparative example and Example 1 is that sodium alcohol ether carboxylate, 2 g of titanate coupling agent, 15 g of isopropanol and 2 g of Artemisia ordosus seed gum are not added in step S5, and the other steps are the same.

[0027] Comparative Example 6 The difference between this comparative example and Example 1 is that in step S6, the mixed material obtained in step S5 is only poured into a mold for pre-forming and pressing, and directly sintered at a constant temperature of 1350° C. for 25 minutes without gradient heating and subsequent cooling treatment.

[0028] Performance Testing: According to GB / T4740-1999 and JC / T2138-2012, the mechanical properties and acid and alkali corrosion resistance of the products obtained in each embodiment and comparative example were tested. The test results are shown in Table 1 below.

[0029] Table 1 Performance test results

[0030] It can be seen from the above performance test results that the bending strength, compressive strength, fracture toughness, and acid and alkali resistance of Examples 1-3 are relatively good. In particular, the comprehensive performance of Example 3 is the most outstanding. Compared with the examples, the comparative examples are significantly worse than the examples in the corresponding performance tests due to the differences in the composition of each component and the preparation process. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0031] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-toughness thermoformed stone basin, characterized in that: The steps include: S1: preparing active composition powder; S2: Preparation of modified kaolin; S3: preparing modified bentonite; S4: preparing a modification aid; S5: In parts by weight, 25-45 parts of the active composition obtained in step S1, 20-40 parts of the modified kaolin obtained in step S2, 15-25 parts of the modified bentonite obtained in step S3, 5-10 parts of the modified auxiliary agent obtained in step S4, 3-6 parts of sodium alcohol ether carboxylate, 2-5 parts of titanate coupling agent, 15-35 parts of isopropanol and 2-6 parts of artemisia seed gum are mixed, and stirred at a temperature of 90-120°C for 30-50 minutes; then 3-6 parts of aluminum silicate, 2-7 parts of lithium tantalate and 3-8 parts of copper calcium titanate are added, and ultrasonic treatment is carried out at a power of 200-400W and a frequency of 85-95kHz for 15-25 minutes; then, a constant temperature refrigeration treatment is carried out at a temperature of 0.2-0.6°C for 75-95 minutes to obtain a mixture; S6: Pour the mixture obtained in step S5 into a mold for pre-forming and pressing, first sinter at a constant temperature of 1100-1250℃ for 15-25min; heat to 1350-1500℃ at a rate of 6-10℃ / min, and continue sintering at a constant temperature for 25-35min; cool to 850-920℃ at a rate of 5-8℃ / min and continue sintering at a constant temperature for 10-16min; then demold, cool to room temperature, grind and polish to obtain the high-toughness hot-formed Zhenshi basin.

2. The method for preparing a high-toughness thermoformed stone basin according to claim 1, characterized in that: The preparation process of the active composition powder in step S1 is as follows: 10-20 parts of wollastonite, 5-10 parts of ultra-white sand, 3-8 parts of feldspar and 2-7 parts of diopside powder are ground to a particle size of 80-100 nm, and subjected to constant temperature steam treatment at a temperature of 280-300° C. for 8-12 min; the temperature is lowered to 105-110° C. at a rate of 8-10° C. / min, and the constant temperature steam treatment is continued for 15-22 min; and then microwave treatment is performed at a power of 200-230 W for 5-10 min, microwave treatment is performed at a power of 560-600 W for 10-15 min, and microwave treatment is performed at a power of 400-430 W for 12-18 min to obtain the active composition powder.

3. The method for preparing a high-toughness thermoformed stone basin according to claim 2, characterized in that: The preparation process of the active composition powder is optimized as follows: 15 parts of wollastonite, 8 parts of ultra-white sand, 6 parts of feldspar and 5 parts of diopside powder are ground to a particle size of 80-100 nm, and subjected to constant temperature steam treatment at a temperature of 290° C. for 10 min; the temperature is lowered to 108° C. at a rate of 9° C. / min, and the constant temperature steam treatment is continued for 18 min; and then microwave treatment is performed at a power of 220 W for 7 min, at a power of 580 W for 12 min, and at a power of 420 W for 15 min to obtain the active composition powder.

4. The method for preparing a high-toughness thermoformed stone basin according to claim 2, characterized in that: The preparation process of the modified kaolin described in step S2 is as follows: crush the kaolin to a particle size of 5-10 μm, add a nitric acid aqueous solution with a mass fraction of 20-35% according to a solid-liquid ratio of 1g:5-8ml, stir evenly, magnetize for 8-16 minutes under a magnetic field strength of 2.2-2.8T, and dry at a temperature of 130-150°C for 25-35 minutes to obtain modified kaolin.

5. The method for preparing a high-toughness thermoformed stone basin according to claim 4, characterized in that: The preparation process of the modified kaolin is optimized as follows: crush the kaolin to a particle size of 5-9 μm, add a 30% by mass nitric acid aqueous solution according to a solid-liquid ratio of 1g:7ml, stir evenly, magnetize for 14 minutes under a magnetic field strength of 2.5T, and dry at a temperature of 140°C for 30 minutes to obtain the modified kaolin.

6. The method for preparing a high-toughness thermoformed stone basin according to claim 2, characterized in that: The preparation process of the modified bentonite in step S3 is as follows: adding bentonite to an ethanol aqueous solution with a mass fraction of 25-35% according to a solid-liquid ratio of 1g:3-7ml and stirring evenly, keeping the temperature at 135-145°C for 8-12min, heating to 220-240°C at a rate of 2-5°C / min and continuing to keep the temperature for 30-40min, cooling to room temperature, immersing in an acetic acid aqueous solution with a mass fraction of 10%-15%, stirring evenly, and drying at a temperature of 100-120°C for 35-45min to obtain the modified bentonite.

7. The method for preparing a high-toughness thermoformed stone basin according to claim 6, characterized in that: The preparation process of the modified bentonite is optimized as follows: adding bentonite to a 30% by mass ethanol aqueous solution at a solid-liquid ratio of 1g:5ml and stirring evenly, maintaining the temperature at 140°C for 10 minutes, heating to 230°C at a rate of 4°C / min and maintaining the temperature for 35 minutes, cooling to room temperature, immersing in a 12% by mass acetic acid aqueous solution and stirring evenly, and drying at 110°C for 40 minutes to obtain the modified bentonite.

8. The method for preparing a high-toughness thermoformed stone basin according to claim 2, characterized in that: The preparation process of the modifying agent described in step S4 is as follows: by weight, 30-50 parts of calcium feldspar, 25-35 parts of mullite, 15-25 parts of calcium feldspar, 10-20 parts of montmorillonite and 1-3 parts of talc are mixed in a ball mill until uniform; after drying, they are loaded into a mold, heated to 1300-1500°C at a rate of 5-10°C / min, and kept warm for reaction for 35-45min to obtain the modifying agent.

9. The method for preparing a high-toughness thermoformed stone basin according to claim 2, characterized in that: Step S5 is further optimized as follows: in parts by weight, 40 parts of the active composition obtained in step S1, 35 parts of the modified kaolin obtained in step S2, 22 parts of the modified bentonite obtained in step S3, 8 parts of the modified auxiliary agent obtained in step S4, 5 parts of sodium alcohol ether carboxylate, 4 parts of titanate coupling agent, 20 parts of isopropanol and 4 parts of artemisia seed gum are mixed, and stirred at a temperature of 110°C for 45 minutes; then 5 parts of aluminum silicate, 5 parts of lithium tantalate and 6 parts of calcium copper titanate are added, and ultrasonic treatment is carried out at a power of 350 W and a frequency of 92 kHz for 22 minutes; then, a constant temperature refrigeration treatment is carried out at a temperature of 0.4°C for 80 minutes to obtain a mixture.

10. The method for preparing a high-toughness thermoformed stone basin according to claim 2, characterized in that: Step S6 is further optimized as follows: pouring the mixture obtained in step S5 into a mold for pre-forming and pressing, first sintering at a constant temperature of 1200°C for 20 minutes; heating to 1480°C at a rate of 8°C / min, and continuing to sinter at a constant temperature for 28 minutes; cooling to 880°C at a rate of 6°C / min and continuing to sinter at a constant temperature for 12 minutes.

Citation Information

Patent Citations

  • Anti-aging and anti-cracking refractory brick and preparation method thereof

    CN106673676A

  • High-toughness hot-shrinkage-resistant artificial board and preparation method thereof

    CN106928588A

  • High-toughness waterproof rubber material for ball core of baseball

    CN107629343A

  • Flame-retardant fabric for work clothes with high acid and alkali resistance

    CN113308875A

  • Crystal- and jade-like material having gentle white appearance and preparation method therefor

    WO2024082637A1